PENGEMBANGAN MODUL PRAKTIKUM BERBASIS MEDIA BERGAMBAR TEMA PANAS DAN PERPINDAHANNYA PADA SISWA KELAS V SEMESTER II DI SEKOLAH DASAR (Jurnal Sosial Humaniora dan Pendidikan, 2022)
The purpose of this study was to determine the analysis of learning needs, to determine the design or design, to test the validity and to test the practicality of the practicum module based on pictorial media. This research uses Research and Development research type. The model used is the ADDIE development model consisting of 5 stages, namely: (1) analysis stage, (2) design stage, (3) develop stage, (4) implementation and evaluation stage and 4 stages of which are used in this study. The finished module is validated by 3 validators, namely: language validator, design validator, and material validator. The results of the validation are then analyzed to determine the validity of the product, it is very valid with a percentage of 89%. The results are evidenced by the value of material experts 87.5%, the value of linguists 96.8%, the value of design experts 82.5%.